Interference With Complex IV as a Model of Age-Related Decline in Synaptic Connectivity - Kriebel, Martin; Ebel, Julia; Battke, Florian; Griesbach, Stefan; Volkmer, Hansjürgen (Frontiers in Molecular Neuroscience, 2020)
Age-related impairment of mitochondrial function may negatively impact energy-demanding processes such as synaptic transmission thereby triggering cognitive decline and processes of neurodegeneration. Here, we present a novel model for age-related mitochondrial impairment based on partial inhibition of cytochrome c oxidase subunit 4 (Cox4) of complex IV of the respiratory chain. miRNA-mediated knockdown of Cox4 correlated with a marked reduction in excitatory and inhibitory synaptic marker densities in vitro and in vivo as well as an impairment of neuronal network activity in primary neuronal cultures. Transcriptome analysis identified deregulation of gene clusters, which link induced mitochondrial perturbation to impaired synaptic function and plasticity as well as processes of aging. In conclusion, the model of Cox4 deficiency reflects aspects of age-related dementia and might therefore serve as a novel test system for drug development.